Diverse Seizure Presentation of Acute Mycoplasma Pneumoniae Encephalitis Resolving With Immunotherapy. (April 2014) - Arkilo, Dimitrios; Pierce, Beth; Ritter, Frank; Doescher, Jason S.; Frost, Michael
We report 3 previously normal children that presented for evaluation of new onset seizures. Case 1, a 7-year-old female, presented with refractory left frontal lobe seizures associated with right arm simple motor seizures refractory to 6 antiepileptic medications at sufficient doses and levels. Case 2, a 15-year-old female, presented with left frontotemporal lobe seizures and nonconvulsive seizures, associated with neuropsychiatric symptoms refractory to 5 antiepileptic medications. Both patients received intravenous steroids and intravenous immunoglobulin. Case 3, an 11-year-old male, presented with a generalized tonic clonic seizure and worsening hallucinations responding to intravenous corticosteroids and 1 antiepileptic medication. All 3 patients had extensive infectious and metabolic evaluation and were found to be serum immunoglobulin M positive for mycoplasma pneumoniae . Despite their prolonged severe symptoms, all patients had virtually complete recovery with excellent seizure control after aggressive seizure management with immunotherapy and antiepileptic medication.